Diagnostic Test of FNAB Towards Histopathology in Lipoma Soft Tissue Tumor Patients: Uji Diagnosis FNAB Terhadap Histopatologi Pada Pasien Tumor Jaringan Lunak Lipoma - Jihan Azzahra Arsyi; Handayati, Anik; Sri Sulami Endah Astuti (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Lipomas are the most common soft tissue tumor neoplasms. Their range from benign lipomas to high grade liposarcomas. Liposarcoma happens when the neoplasm of a lipoma is malignant. There are various diagnostic methods that can be used to evaluate lipomas, one of which is Fine Needle Aspiration Biopsy (FNAB). FNAB is the initial diagnosis to determine the diagnosis of lipoma soft tissue tumors. Histopathology is the definitive diagnosis or the gold standard for diagnosing lipoma soft tissue tumors. This research aims to determine the value of the Fine Needle Aspiration Biopsy diagnostic test against histopathological tests as the gold standard in lipoma soft tissue tumor patients. This research is a retrospective with a descriptive observational design. This research involved taking medical records of patients with lipoma soft tissue tumors who were examined by FNAB at RSPAL dr. Ramelan, Surabaya for the period August 2019 - December 2021. The results of the FNAB examination were then matched against the histopathological examination data as the gold standard. Data processing using 2x2 cross tabulation to calculate the diagnostic test which includes sensitivity, specificity, positive predictive value, negative predictive value, and accuracy against the gold standard. The results of the Fine Needle Aspiration Biopsy diagnostic test for histopathology in soft tissue lipoma tumors obtained sensitivity of 100.00%, specificity 95.83%, positive predictive value (NRP) 87.5%, negative predictive value (NRN) 100.00%, and 96.77% accuracy. Fine Needle Aspiration Biopsy (FNAB) has good diagnostic value for diagnosing lipoma soft tissue tumors.